A longitudinal study of positive mental health and coping among Indigenous adults with type 2 diabetes. Issue 3 (4th May 2023) - Sittner, Kelley J.; Herman, Kaley A.; Gonzalez, Miigis B.; Walls, Melissa L.
ABSTRACT: Objective: Indigenous Peoples and scholars call for strengths-based approaches to research inclusive of Indigenous resiliency and positive outcomes. The purpose of this study was to examine positive mental health for Indigenous adults with type 2 diabetes and to determine if positive mental health is linked to community connectedness (a coping resource) and active coping (a coping response). Methods: Participants (N  = 194 at baseline) were randomly selected from clinical records, at least 18 years old with a type 2 diabetes diagnosis, and self-identified as American Indian. Results: Latent growth curve models revealed that average positive mental health was predicted to decrease over the four waves of the study, although not for participants with above-average active coping at baseline. Community connectedness at baseline was associated with higher initial levels of positive mental health. Within-person change in active coping and community connectedness were both associated with increases in positive mental health. Conclusion: This study aligns with previous research demonstrating that coping can influence health outcomes, and furthers the stress process literature by showing that active coping and community connectedness can impact positive mental health for Indigenous adults with Type 2 Diabetes.